ANALISIS PROYEKSI CASH FLOW Studi Pada PT Askes (Persero) - , Usfuriyah Nur Ainiyah ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Cash is the most liquid asset for the companies that have a central position in an effort to maintain the operation of the company, so that each company will strive to provide cash in ideal position. This study aims to analyze the condition of the company Net Cash Flow during the last three years,ie 2009, 2010, and 2011 and determine investment opportunities in the next two years, which is 2012 and 2013 after the company used cash to meet obligations to a third party, in this case to meet the health care claim payment and financing the operations. The method of data analysis used is the trend analysis that is an analytical method that is intended to make an estimation or forecast of the future by using time series analysis, the method is Least Square Method. The object of research is PT Askes (Persero), it is because based on Law Number 24 of 2011 on the Implementation of the Social Security Agency, in 2014 PT Askes (Persero) will be dissolved and turned into BPJS Health, the management of professional personnel will get serious attention, especially because it involves on the management of a very large fund, so it is necessary to analyze the projection of cash flow at PT Askes (Persero). The results showed that the condition of the net cash flow or excess funds from operating activities, investing activities and financing activities of the company during the last three years, ie 2009, 2010, and 2011 fluctuated that is influenced by the company's operating activities dominated by premium income and payment of health care costs. In addition, the total in 2012 the company has investment opportunity for Rp 10.284.128.549.914, although in the first quarter deficit of Rp 917.342.104.934 with details in January 2012 amounted to Rp 336.890.237.356, in February 2012 amounted to Rp 460.746.515.512 and March 2013 amounted to Rp 119.705.352.066. Whereas in 2013 the company has increasing investment opportunities compared to 2012 for Rp 25.473.198.588.188. Cash flow projection analysis needs to be done by PT Askes (Persero) before committing cash planning, in order to obtain sufficient and accurate guidelines in making decision on optimal control of the companyâs cash flow.